Perancangan Sistem Antisipasi Terhadap Luapan Air Pada Selokan Berbasis Internet Of Things - I Nyoman Jepri Martana; I Wayan Sudiarsa; Ayu Manik Dirgayusari; I Gede Adnyana (Jurnal Tika, 2022)
The impact of overflowing water in this ditch is the emergence of many diseases in the community and of course activities will be hampered. Because the possibility of flooding caused by overflow in the ditch, it is hoped that there will be a system that can reduce or even prevent flooding in areas that are prone to flooding due to overflowing sewers. As is the case with the problem at one location in Petak Kelod Village, precisely in Banjar Madangan Kaja, which experienced a problem in the gutter that almost every heavy rain came, causing the sewer to be clogged due to several factors such as: the size of the ditch is not the same which causes the water flow to become blocked, then the garbage in the gutter also causes the flowing water to become clogged. To overcome this, we need a system that can drain the blocked water flow by flowing it towards a larger ditch so as to make the clogged sewer smoother. The systems used to support this research are Arduino Uno, NodeMCU ESP8266, Ultrasonic Sensors, LEDs, and Stepper Motors, where the system will send the water level status via telegram and open the door automatically if the water level threshold is reached to be channeled to the backup channel so that the water is divided into two with the same volume and causes the waterway to return to normal. In the Esp8266 NodeMCU Connection Testing test, 100% success was obtained with an error of 6.934% in ultrasonic sensor testing, overall system performance was measured and 100% success was obtained